Public Cardio Pulmonary Resuscitation Simulation Training on Self-Efficacy in Society - Santy Sanusi; Angga Wilandika; Dian Rismawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of lay cardiopulmonary resuscitation simulation method training on self-efficacy in the management of lay cardiopulmonary resuscitation in the community. The method used is a one-group pre-post test design with convenience sampling. The results showed that the significance value of self-efficacy before and after the intervention was 0.001 (p-value <0.05). In conclusion, there is an effect of layman's CPR simulation training on community self-efficacy. This training can be an alternative for health workers to increase people's self-efficacy beliefs in CPR. Keywords: Self Efficacy, Cardiac Arrest, Community, Cardio Pulmonary Resuscitation